Oral Health Advocacy Education Impacts Future Engagement: Exploration at a Midwestern US Dental School - Amini, Homa; Wells, Alexander J.; Boynton, James R.; Guo, Xiaohan; Ni, Ai (Frontiers in Oral Health, 2021)
Purpose: With the emergence of COVID-19, and the potential inclusion of dental benefits in Medicare, it is critical that dentists are able to engage in legislative advocacy to support public oral health. Dental education has an opportunity to teach advocacy skills to future dentists, although advocacy training in predoctoral dental education has been largely ignored. The purpose of this study was to evaluate fourth-year dental student's attitudes toward advocacy, identify the type and extent of advocacy experiences during dental school, and assess their future intentions to engage in advocacy. Methods: An electronic questionnaire was administered to fourth-year dental students enrolled in their final semester at Ohio State University. Results: Forty-seven students completed the survey (43% response rate). Most (84%) respondents agreed that advocacy training should be a required experience in accreditation standards for predoctoral dental education. Over half (58%) reported seldom or no exposure to legislative and regulatory processes in oral health policy development in the curriculum. Students who participated in grassroots advocacy efforts while in dental school were more likely to contact legislators regarding dental issues (p = 0.005) or public insurance (p = 0.037), and participate in future lobbying efforts (p = 0.019). Students who contributed to PAC while in dental school were more likely to express intentions to contribute in future (p = 0.005). Conclusions: There is limited exposure to legislative advocacy in predoctoral dental education. Dental students with advocacy experience are more likely to report intentions to participate in advocacy as dentists. Dental education has a critical role in preparing future dentist-advocates.